Non-condom use among female nurses in Zambia - Siziya, Seter; Hakim, J.G.; Chideme Maradzika, J.; Rusakaniko, S.; Matchaba-Hove, Reginald (2016)
To estimate non-condom user rate and to characterize non-condom users among female nurses.Cross sectional.Health institutions.Data from 640 (86.5pc) out of 740 consenting female nurses were available for analyses.Non-condom user rate.Non-condom user rate (per 100) among the female nurses was 73.1pc (95pc CI69.7 to 76.5). Non-condom users tended to be aged above 30 years (OR 1.57; 95pc CI 1.02 to 2.40), midwives (OR 1.56; 95pc CI 1.03 to 2.37), married (OR 2.70; 95pc CI 1.73 to 4.21), not to think that spouse/partner has had sex with other partners (OR 1.72; 95pc CI 1.11 to 2.68) and to have had a sexually transmitted disease (OR 2.61; 95pc CI 1.25 to 5.43).There was a surprising high level of non-condom users among female nurses, probably due to the inability for females to initiate or negotiate condom use.